The role of labour standards in shaping migration: the ASEAN perspectives - Kar, Yee Ng; Rusmawati Said, (Penerbit Universiti Kebangsaan Malaysia, 2015)
This study attempts to investigate the role of labour standards in explaining the pattern of bilateral migration flows in ASEAN; and it is motivated by the target of ASEAN Economic Community Blueprint that aims to promote free flow of skilled labour in the region. To answer the research question, this paper used a panel data set consisting 45 countries and applied pooled ordinary least squares technique for the empirical analysis. The study proxies labour standards with four different indicators: number of strikes, average actual weekly hours worked, cases of occupational injuries, and trade union density rate. Interestingly, the analysis obtained mixed results to explain the effect of labour standards on bilateral migration flows in ASEAN countries, depending on what indicator being used to measure the level of labour standards in the empirical analysis. When the level of labour standards was represented by number of strikes and/ or average weekly hours worked, the results demonstrated that better labour standards increase the bilateral migration flows among countries selected in the analysis. Nonetheless, the migration increased when there were more cases of occupational injuries reported, which implies that better working conditions do not attract workers to move. The findings suggest that governments should review and improve the existing labour policies in order to attract immigrants, especially those high-skilled.